Framing Gender-Based Violence in Tanzanian Newspapers: A Content Analysis of the Citizen and Daily News Newspapers during the 2024 16 Days of Activism Campaign - Chrispine Francis Lwoga,; Kaanaeli Kaale,; Peter C. Mataba, (Technium Social Sciences Journal, 2026)
This study examined how The Citizen and Daily News newspapers framed gender-based violence (GBV) during the 2024 16 Days of Activism campaign in Tanzania. Guided by framing theory and using a qualitative research design, the study conducted a systematic content analysis of GBV-related stories published between November and December 2024. Through thematic analysis, the study identified the dominant frames, narratives, and tonal patterns used in reporting GBV. Findings revealed five major frames: victimization, human rights, advocacy and community mobilization, perpetrator-blame and the criminal justice frame, and a mixed empowerment-and-reform frame. Both newspapers highlighted GBV as a violation of human rights and a barrier to gender equality, though differences emerged regarding tone and emphasis. The Citizen frequently combined victim-centered storytelling with empowerment narratives, while Daily News tended to promote institutional accountability, policy implementation, and community responsibility. The newspapers also emphasized themes such as women’s empowerment, legal reforms, social responsibility, and survivor support. The study concludes that while the selected newspapers contribute to raising awareness on GBV, gaps remain in addressing structural causes and advancing transformative gender discourse. The findings are valuable for media practitioners, policymakers, and activists seeking to strengthen ethical and effective media framing of GBV in Tanzania.